Odpowiedzi

2010-03-22T14:32:04+01:00
2(x-3)+3(4-x)=5
2x-6+12-4x=5
-2x-18=5 /+18
-2x=23 /: 2
x=11,5


3(x-4)-2(2x-5)=-4
3x-12-4x-10=-4
-x-2=-4 /+2
-x=-2 /razy -1
x=2
3 2 3
Najlepsza Odpowiedź!
2010-03-22T14:38:13+01:00
1. 2(x-3)+3(4-x)=5
2x-3x=5+6-12
-x=-1/:-1
x=1
2. 3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
3x-4x=-4+12-10
-x=-2/:-1
x=2
3. x/3-5/6=1/12-x/2 /*12
4x-10=1-6x
4x+6x=1+10
10x=11/:10
x=11/10=jeden i jedna dziesiąta
4. x/2-3/4=7/8+x/4 /*8
4x-6=7+2x
4x-2x=7+6
2x=13/:2
x=6.5
2 5 2
2010-03-22T14:44:32+01:00
2(x-3)+3(4-x)=5
2x-6+12-3x=5
2x-3x=5+6-12
-x=11-12
-x=-1


3(x-4)-2(2x-5)=-4
3x-12-4x-10=-4
3x-4x=-4+12+10
-x=18

x/3-5/6=1/12-x/2 /*12
12(x/6)-12(5/6)=12(1/12)-12(x/2)
2x-10=1-6x
2x+6x=1+10
8x=11/8
x=1 i 3/8


x/2-3/4=7/8+x/4 -pomnożyc przez 8
8(x/2)-8(3/4)=8(7/8)+8(x/4)
4x-6=7+2x
4x-2x=7=6
2x=13 podzielić przez 2
x=6,5





1 5 1